Descrição de uma nova espécie de Cordiluroides Albuquerque (Diptera, Muscidae, Coenosiinae) - Couri,Márcia Souto (2002)
Description of a new species of Cordiluroides Albuquerque (Diptera, Muscidae, Coenosiinae). Cordiluroides paulistensis sp. nov. from Salesopolis, São Paulo, Brazil is described and illustrated.